KERUNTUHAN JEMBATAN AKIBAT KEGAGALAN PELAT BUHUL PADA SAMBUNGAN JEMBATAN RANGKA BAJA (Studi Kasus: Jembatan I-35W MISSISIPI) - Anis Rosyidah; Johanes Adhijoso Tjondro (Politeknik Negeri Jakarta, 2018)
ABSTRACTThe collapse of Minnesota Bridge number 9340 or I-35W bridge on August 1, 2007, is indeed surprising considering the maintenance of the bridge conducted regularly. The bridge was designed in the early 1960s using AASHO